THE MEANING OF REVOLUTION IN AMIN AR-RAYHANI’S ESSAYS - Lesmana, Maman; Ilahiyah, Ikhfy Kanzan (Universitas Islam Sumatera Utara (UISU), 2023)
This study discusses the meaning of revolution in Amin Ar-Rayhani's essays in the book of Ar-Ar-Rayhaniyyāt (The Ar-Rayhani Essays) entitled Ats-Tsauratu Al-Ifransiyyatu (French Revolution) and Ats-Tsauratu Al-Ḥaqīqiyyatu (The Real Revolution) . The two essays are discussed in this study with a revolutionary theory approach. The purpose of this research is to explain the meaning of revolution in his two essays. The research method used by the researchers is a qualitative research method with a historical approach. The main data are obtained from the above-mentioned essays and then the secondary data are from books, articles, journals, theses, and other scientific works. The theory used in this study comes from the six types of revolution put forward by Chalmers Johnson. Based on the results of the research, the first essay is included in the argumentation essay and the second one in the narrative essay. Both essays are categorized under the type of revolution of conspirational coup de'Etat.